If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6 + -1x + -4 = 10 + -1x Reorder the terms: 6 + -4 + x + -1x = 10 + -1x Combine like terms: 6 + -4 = 2 2 + x + -1x = 10 + -1x Combine like terms: x + -1x = 0 2 + 0 = 10 + -1x 2 = 10 + -1x Solving 2 = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + x = 10 + -1x + x Combine like terms: -1x + x = 0 2 + x = 10 + 0 2 + x = 10 Add '-2' to each side of the equation. 2 + -2 + x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + x = 10 + -2 x = 10 + -2 Combine like terms: 10 + -2 = 8 x = 8 Simplifying x = 8
| 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 | | -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 | | -2x+12-2x=-5(x-2)+2 | | 3x+5x=850 | | 12+10=14y-3y | | -2x+10-3x=-5(x-2)+2 | | 8-6x-3=-21+4x-14 | | 7(x+2)=9x+2 | | 2(1x+8)=12 | | 6x^2-12=5x^2-4x | | X/12=34 | | -1x+12-3x=-5(x-2)+2 | | 18y^2-7y-2=0 | | 4x-x+9=(x+2)+p | | g(-1)forg(t)=(t^2-1)(t+4) | | 4n-2=4n-6 | | -2x+11-3x=-5(x-2)+2 | | 4+77x=44x+16 | | X-(-8)=15.6 | | 2x+6=-22-5x | | -2x+12-3x=-5(x-2)+2 | | 5(-3+6x)=-15 | | -1/3-g=-1/3 | | 8w-17w=18 | | 3e^2x+5=15 |